Primeiro registro de Nipaecoccus nipae (Maskell, 1893) (Hemiptera: Pseudococcidae) em Euterpe precatoria Martius (Arecaceae) no Brasil - Santos, Rodrigo S.; Peronti, Ana L. B. G. (Entomological Communications, 2023)
Euterpe precatoria Martius, 1824 is a palm tree of great socioeconomic importance for the northern region of Brazil, whose heart of palm and fruits are economically exploited. For the expansion of its cultivation in commercial plantations, there is a need to know the phytosanitary aspects of the crop, especially the associated insect pests. Thus, this work aimed was to record the scale insect Nipaecoccus nipae (Maskell, 1893) (Hemiptera: Pseudococcidae) infesting E. precatoria. Populations of this species were observed on E. precatoria plants in Rio Branco, state of Acre, Brazil. Thus, this is the first record of N. nipae on single açaí palm tree in the state of Acre and Brazil. Due to the socioeconomic importance of this palm for the North region and the damaging potential of N. nipae, further studies are strongly recommended in order to determine the level of damage and control alternatives.